Respiratory syncytial virus NS1 protein degrades STAT2 by using the elongin-cullin E3 ligase - Stevenson, Nigel (My University, 2007)
Respiratory syncytial virus (RSV) infection causes bronchiolitis and pneumonia in infants. RSV has a linear single-stranded RNA genome encoding 11 proteins, 2 of which are nonstructural (NS1 and NS2). RSV specifically down regulates STAT2 protein expression, thus enabling the virus to evade the host type I interferon response. Degradation of STAT2 requires proteasomal activity and is dependent on the expression of RSV NS1and NS2 (NS1/2). Here we investigate whether RSV NS proteins can assemble ubiquitin ligase (E3) enzymesto target STAT2 to the proteasome. We demonstrate that NS1 contains elongin C and cullin 2 bindingconsensus sequences and can interact with elongin C and cullin 2 in vitro; therefore, NS1 has the potential toact as an E3 ligase. By knocking down expression of specific endogenous E3 ligase components using small interfering RNA, NS1/2, or RSV-induced STAT2, degradation is prevented. These results indicate that E3ligase activity is crucial for the ability of RSV to degrade STAT2. These data may provide the basis for therapeutic intervention against RSV and/or logically designed live attenuated RSV vaccines
PUBLISHED
Keywords: Respiratory syncytial virus (RSV); Infection; Proteins; Immunology, Inflammation & Infection